An exploration of growth in computer software micro firms. (4th May 2018) - Falk, Martin; Hagsten, Eva
Abstract : This paper investigates the drivers of growth in Swedish micro firms providing computer services. Analysis is based on linked data from several sources: registers on business, value added tax (VAT) and education as well as from production statistics. ordinary least squares (OLS) estimations, including approximately 7000 computer service micro firms, show that initial relative labor productivity of micro firms (compared to that of large firms) is significantly positively related to subsequent employment growth in the two following years. Furthermore, exporting micro firms grow faster than those that only sell on the domestic market. The link between exporting and firm growth is higher for export starters. Separate estimations for young micro firms confirm the positive relationships for both exporting and initial productivity. However, share of workers with a tertiary degree is not significantly related to the employment growth of micro firms. Quantile regressions reveal that both exporting and the initial productivity level are particularly important for high-growth micro firms.